Corruptionary disyonaryo ng mga salitang korapsyon sa Pilipinas = a dictionary of Filipino corruption word - Ilagan, Bonifacio P.; Tuazon, Bobby M.; Dela Torre, Fidel Llagas (Anvil Publishing, 2010)
Filipino dictionary of corrupt and political terms.